Application of the Jigsaw Cooperative Learning Model Assisted by Solar System Scope Simulation to Improve Learning Outcomes of Junior High School Students - Alifatul Fitria; Martini Martini (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Science learning on the subject of Earth and the solar system requires learning strategies that can improve students' conceptual understanding so that their learning outcomes improve. This study aims to analyze student learning outcomes using jigsaw cooperative learning assisted by Solar System Scope simulations to improve junior high school students' learning outcomes on the subject of Earth and the Solar System. This study uses a pre-experimental, one-group pre-test-post-test design. Student learning outcomes were measured using pre- and post-tests with a sample of 32 students from class VII-F MTs Negeri 3 Surabaya, and analysed using N-gain and the Shapiro-Wilk normality test. The statistical test used was a non-parametric test, namely the Wilcoxon test. Student learning outcomes increased, yielding an N-gain score of 0.77, interpreted as “High”. The normality test showed that the data were not normally distributed, so the Wilcoxon test was used. The Wilcoxon test results showed a significant difference after jigsaw cooperative learning assisted by solar system scope simulations. Based on these results, jigsaw cooperative learning, supported by solar system scope simulations, is effective in improving student learning outcomes in Earth and solar system material.